Efektivitas Jaklapor pada Aplikasi Jaki (Jakarta Kini) sebagai Implementasi New Public Service - Aulia Ananda, Nury; Fauziah, Rizki (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
In the 21st century, there has been a paradigm shift of Public Administration to public services in response to globalization and the complexity of people's needs. The UK has implemented public service reform through the Open Public Service program since 2013, while in Indonesia, especially the DKI Jakarta Provincial Government, bureaucratic reform adopts collaborative public services through Jakarta Smart City and the JAKI application as a New Public Service innovation for effective, democratic, and measurable services. The transformation of public services in Jakarta, especially the management of public complaints, occurs through the JAKI application with a one-stop complaint system, shortening the span of service control, increasing effectiveness, and providing community satisfaction. The theoretical foundation includes service effectiveness, the concept of New Public Service (NPS), and the concept of Smart City with the integration of information and communication technology. The formulation of the research problem discusses the evaluation of the effectiveness of handling complaints through the JAKI application and the factors that influence it with qualitative methods using questionnaires, documentation, and literature studies. Data was obtained from JAKI users in Jakarta and information sources from Jakarta Smart City, journals, and other secondary data. The results of the study are expected to provide insights for the improvement and development of public services in the digital era.